Use of compulsory community treatment in mental healthcare: An integrative review of stakeholders’ opinions - de Waardt, Dieuwertje Anna; van Melle, Anne Laura; Widdershoven, Guy Antoine Marie; Bramer, Wichor Matthijs; van der Heijden, Franciscus Martinus Machiel Adrianus; Rugkåsa, Jorun; Mulder, Cornelis Lambert (Frontiers in Psychiatry, 2022)
Background: Multiple studies have examined the effects of compulsory community treatment (CCT), amongst them there were three randomized controlled trials (RCT). Overall, they do not find that CCT affects clinical outcomes or reduces the number or duration of hospital admissions more than voluntary care does. Despite these negative findings, in many countries CCT is still used. One of the reasons may be that stakeholders favour a mental health system including CCT. Aim: This integrative review investigated the opinions of stakeholders (patients, significant others, mental health workers and policy makers) about the use of CCT. Methods: We performed an integrative review; to include all qualitative and quantitative papers on the views of patients, significant others, clinicians and policy makers regarding the use of CCT, we searched MEDLINE, EMBASE, PsycINFO, CINAHL, Web of Science Core Collection, Cochrane CENTRAL Register of Controlled Trials (via Wiley) and Google Scholar. Results: We found 142 studies investigating the opinion of stakeholders (patients, significant others and mental health workers) of which 55 were included. Of these 55 studies, 29 included opinions of patients, 14 included significant others, and 31 included mental health care workers. We found no studies that included policy makers. The majority in two of the three stakeholder groups (relatives and mental health workers) seemed to support a system that used CCT. Patients were more hesitant, but they generally preferred CCT over admission. All stakeholder groups expressed ambivalence. Their opinions did not differ clearly between those who did and did not have experience with CCT. Advantages mentioned most regarded accessibility of care and a way to remain in contact with patients, especially during times of crisis or deterioration. The most mentioned disadvantage by all stakeholder groups was that CCT restricted autonomy and was coercive. Other disadvantages mentioned were that CCT was stigmatizing and that it focused too much on medication. Conclusion: Stakeholders had mixed opinions regarding CCT. While a majority seemed to support the use of CCT, they also had concerns, especially regarding the restrictions CCT imposed on patients´ freedom and autonomy, stigmatization, and the focus on medication.